Spidey and his Amazing Friends (London, 2021)
Save the day with Spidey, Ghost-Spider, and Miles Morales as you search for hidden things in 7 scenes! Then flip to the end of the book for even more Look and Find challenges. Learning concepts include counting, rhyming, shapes, and more! - back cover.
Keywords: Spider-Man; (Fictitious character); Pictorial works; Juvenile fiction; Picture puzzles; Juvenile literature